2020
DOI: 10.3168/jds.2020-18208
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: High-throughput sequencing approach to investigate Italian artisanal cheese production

Abstract: In this study, high-throughput sequencing (HTS) was used to investigate the microbiota of Robiola di Roccaverano production, an artisanal Protected Designation of Origin soft cheese made with raw goat milk by addition of a natural milk starter (NMS), from the Piedmont region of Italy. Different steps of production of Robiola di Roccaverano cheese at one artisanal dairy were monitored. Matched samples of milk, NMS, curd, and 5-d and 15-d matured cheeses were collected at different periods of the year. The DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The Krokmatch's microbiota was revealed to be quite unusual, presenting dominant and subdominant species never reported for a cheese till now, like K. georgiana, Aeromonas sp., Klebsiella sp., A. kunkeei or Megamonas sp. Uncommon cheese microbiotas have been reported for some artisanal dairy products (Biolcati et al 2020;Thanzami and Lalhlenmawia 2020;Rabêlo et al 2021) an interesting similarity with the Krokmach is that it has been reported for an open fermentation process, where it is supposed to be related to the flavour (Ding et al 2021). The presence of A. kunkeei could be attributed most easily to environmental contamination, yet some scepticism about this hypothesis is supported by its ability to thrive for months within the Krokmach, as well by the number of its OTU counts, placing it among the subdominant species.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The Krokmatch's microbiota was revealed to be quite unusual, presenting dominant and subdominant species never reported for a cheese till now, like K. georgiana, Aeromonas sp., Klebsiella sp., A. kunkeei or Megamonas sp. Uncommon cheese microbiotas have been reported for some artisanal dairy products (Biolcati et al 2020;Thanzami and Lalhlenmawia 2020;Rabêlo et al 2021) an interesting similarity with the Krokmach is that it has been reported for an open fermentation process, where it is supposed to be related to the flavour (Ding et al 2021). The presence of A. kunkeei could be attributed most easily to environmental contamination, yet some scepticism about this hypothesis is supported by its ability to thrive for months within the Krokmach, as well by the number of its OTU counts, placing it among the subdominant species.…”
Section: Discussionmentioning
confidence: 85%
“…Uncommon cheese microbiotas have been reported for some artisanal dairy products (Biolcati et al . 2020; Thanzami and Lalhlenmawia 2020; Rabêlo et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The recent application of high-throughput DNA sequencing (HTS) supports a detailed analysis of the composition and functional potential of the microbiota of traditional raw milk cheeses. Bacterial communities differ among raw milk cheeses depending on the manufacturing process, but the bacteria in the cheese core are dominated by LAB belonging to the genera Lactococcus , Lactobacillus , Enterococcus , Streptococcus , and Leuconostoc [ 4 , 7 , 8 , 60 , 62 , 63 , 64 ].…”
Section: Main Lab Identified In Raw-milk Artisanal Cheesesmentioning
confidence: 99%
“…Since these cheeses have more intense and unique flavors compared to cheeses manufactured from pasteurized milk, there has been an increased interest in studying the functional and structural diversity of NSLAB. Several studies have attempted to comprehensively describe the microbiota in traditional cheeses at different stages of the ripening process [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Culture-dependent methods are most commonly used, but they are labor-intensive and inherently biased [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, at least 50% of the milk used for the production must be goat's milk. During manufacturing process, thermization process are not allowed and natural milk cultures (NMC) containing mainly Lactococcus lactis are inoculated together with animal rennet for curd formation [12][13][14]. NMC is obtained by back-slopping process where a small amount of the previous days fermented milk is inoculated into fresh milk to start the fermentation process.…”
Section: Introductionmentioning
confidence: 99%